ANALISIS KUALITAS PELAYANAN PRAMUWISATA DI ISTANA ASSERAYAH HASYIMIAH SIAK SRI INDRAPURA - Tanjung, Suheri; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The This research aims to find out how the quality service of the tour guide in the palace Asserayah Hasyimiah Siak Sri Indrapura.This research used qualitative desciptive method to analyze the problems. The sample in this research are 100 samples by using accidental sampling. And then the techniques to collected data in this research are using observation, questionnaire and interview. And it was using likert scale to know the length of intervals.Based on the result of the research that’s been done, it looks that the quality service tour guide in the palace Asserayah Hasyimiah still low and need to be improved again.Keywords : Service Quality, Tour Guide, The Palace Asserayah Hasyimiah